Autosplenectomy in a Patient with Paroxysmal Nocturnal Hemoglobinuria (PNH) - Ethan Burns; Kartik Anand; Gonzalo Acosta; Malcolm Irani; Betty Chung; Abhishek Maiti; Ibrahim Ibrahim; Lawrence Rice (Case Reports in Hematology)
Autosplenectomy (AS) is a known complication of diseases such as sickle cell anemia, celiac disease, and inflammatory bowel disease. We report the first known case of AS due to paroxysmal nocturnal hemoglobinuria (PNH). A 24-year-old Caucasian male had evidence of hemolytic anemia at the age of 14 and was diagnosed with PNH at the age of 16. He had recurrent episodes of sepsis due to dialysis line infections from poor hygiene, and blood cultures had been positive for multiple organisms including Staphylococcus aureus, Enterococcus faecalis, and Streptococcus pneumoniae. The patient’s peripheral blood smears since the age of 14 years demonstrated Howell–Jolly bodies in conjunction with thrombocytopenia and hemolytic anemia, but abdominal ultrasonography reported a normal appearing spleen. The patient presented with septicemia two years after starting eculizumab, and his peripheral blood smear showed extensive Howell–Jolly bodies, Pappenheimer bodies, acanthocytes, and target cells. Splenic ultrasonography demonstrated an atrophic spleen with multifocal scarring, and absent splenic uptake of liver-spleen scintigraphy, consistent with AS. Clinicians should remain vigilant of the potential sequelae of PNH and consider the possibility of the development of AS.